THE EFFECT OF VARIATIONS IN CURING TEMPERATURE OF CARBON FIBER/PVC FOAM BOARD SANDWICH COMPOSITES ON BENDING TEST FAILURE ANALYSIS - paundra, fajar; Saputra, Rizky; Pujiyulianto, Eko; Arif, Muhamad Fatikul; Muhyi, Abdul (Jurnal Pendidikan Teknik Mesin, 2024)
Curing is a method to improve the ability of sandwich composite materials by heating the sandwich composite in an electric oven for a certain time and temperature. This research aims to observe and analyze the effect of curing temperature on bending strength and elastic modulus as well as analyzing the fracture results of sandwich composites. The materials used are polyester resin, 240 gsm twill carbon fiber and PVC foam core with a thickness of 5 mm. The manufacturing method used is vacuum bagging and the curing process is carried out with temperature variations of 70°C, 80°C and without curing for 1 hour. The test carried out is a bending test using the ASTM C393 standard. The maximum bending strength value of the sandwich composite is found at a curing temperature of 80°C, namely 48.35 MPa, while the lowest bending strength value is found in the variation without curing, namely 30.07 MPa. The highest elastic modulus value is also found at a curing temperature of 80°C, namely 67.03 GPa and the lowest elastic modulus value is also found in the variation without curing, namely 33.67 GPa.